55 A Highly Effective Technique for Transseptal Endocardial Left Ventricular Lead Placement for Delivery of Cardiac Resynchronisation Therapy. (6th June 2015) - Domenichini, Giulia; Diab, Ihab; Campbell, Niall; Dhinoja, Mehul; Hunter, Ross; Sporton, Simon; Earley, Mark; Schilling, Richard
Abstract : Introduction: Endocardial transseptal left ventricular (LV) lead delivery is challenging due to the absence of dedicated equipment designed for this procedure. We describe a new technique for delivery of a transseptal LV lead. Methods: Patients (pts) with class 1 indication for CRT and a previous failed attempt at conventional LV lead placement via the coronary sinus were offered this procedure. All pts were anticoagulated with Warfarin. The implantation technique is shown in the Figure 1 . A left subclavian and right femoral venous access are initially obtained. A: a gooseneck snare (a) is opened in the right atrium (RA) through which an Endry's needle and Mullin's sheath (b) are advanced into the RA. B: a transseptal puncture is made and a wire is placed in the left upper pulmonary vein. C: the snare is advanced into the left atrium (LA) and an Attain sheath is advanced over the snare. D: the snare is removed leaving the Attain sheath in the LA. E: an active fixation lead is advanced through the sheath into the LV and screwed into the lateral wall. The sheath is split and removed F: all three LV leads are seen: (c) a previous transvenous lead, (d) a surgical epicardial lead and (e) the new active fixation lead. Results: The procedure was performed successfully in all 12 pts attempted. The median procedure and fluoroscopy time were 148 min (IQR 113–176) and 16 min (IQR 10–19). Endocardial LV lead electrical parameters were satisfactory at implant and stable over time. The only complication was a pocket haematoma in a pt with a sub-pectoral generator. There was no need for repeat procedures after a median follow-up of 97 days (IQR 36–250). Conclusions: This approach provides a reliable and effective alternative technique for delivery of an endocardial LV lead inserted transseptally into the LV.